Kísérlet a bárdudvarnok-szentbenedeki premontrei prépostság környezeti rekonstrukciójára - Aradi, Csilla M.; Molnár, István (Genius loci – Laszlovszky 60, 2018)
[An attempt to reconstruct the environment of the Premonstratensian abbey of Bárdudvarnok-Szentbenedek]
Num Pages: 407 Pp.
Keywords: kaposfő

Az ócsai premontrei prépostság régészeti kutatása - Csoltkó, Emese (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The village of Ócsa is situated to the south of Budapest in Pest County. The first mention of the existence of the Premonstratensian provostry is dated to 1234 in the so-called Catalogue of Ninive, which mentions that Ócsa is the filial of the convent of Jászó ( Jasov, Slovakia). The church with three naves and two towers at its western facade was built in the first half of the 13th century. During the construction works there were some modifications in the original plans, as the church was planned with another vaulting section towards at the west, but that was, along with the vaulting of the naves, never finished. Minor reconstruction works can be dated to the Middle Ages; for example wall-paintings and the Gothic pastoforium. The Premonstratensians left Ócsa before the Ottoman occupation period, but as a parish church, it didn’t lose the function which is attested by the 15th century demolition of the rood-screen. The church was used by the Calvinist congregation since 1560. As part of the preparation for the reconstruction works, there was archaeological research between 1986 and 1992 which was led by Juan Cabello. This included a systematic, full-scale excavation in the church and in the churchyard. In the course of the excavation, the monastery building with the one side and three pit houses from the 12th–13th century was found. The surrounding and inside of the church were used as a cemetery. The first reconstruction work was realized in the second half of the 18th century ( József Teleki’s works between 1774 and 1777). In the 18th century the church was damaged by natural disasters like lightning and fire. Thus another renovation was necessary, led by Ottó Tandor (1897–1900). In 1909 Ottó Sztehlo renewed the damaged northern portal. The elevation of the towers of the church was carried out by Ernő Foerk in 1923. Finally, the recent renovation of the church was conducted by Tibor Gál between 1989 and 1995.
Keywords: ócsa

Szent Euszták és vértanú társai prépostság | Háros-sziget, Budapest XXII. - Galuska, Tünde (A pálos rend építészeti emlékei, 2018)
Keywords: csút

Adalékok a jászói Keresztelo Szent János premontrei monostor középkori történelméhez - Kotrusová, Júlia (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The Monastery of St. John the Baptist in Jasov belongs among the oldest Premonstratensian monasteries in modern Slovakia. The circumstances surrounding the arrival of Premonstratensians in Jasov and the year of foundation of the monastery are amongst the most debated problems in the history of the Jasov provostship. The source of these controversies is the fact that the foundation charter was not preserved. The opinions of historians on the foundation of the monastery vary. A number of historians assume that it was founded at the turn of the 12th and 13th centuries, possibly at the beginning of the 13th century. I argue that a charter issued by King Béla IV in 1255 can contribute to clarification of the foundation of the convent. The document re-establishes the originalprivileges of the monastery. The earliest references to Premonstratensian monasteries in Hungary is preserved in the Ninive catalogue, specifically in its second registry. The properties of the monastery also raise a number of questions. The institution owned properties of high value in the Middle Ages. The oldest mention of their estate possession dates back to the above mentioned charter issued by King Béla IV in 1255. The lands mentioned in the charter were compact. Besides the original property described by the charter, in 1255 lands were provided for the monastery that Béla acquired from Duke Coloman. During the medieval and early modern period Jasov was a central property of the Jasov provostship. Due to its location and its vicinity to the monastery, it became more and more prominent in the 13th century, when it gained urban privileges, most importantly market rights.
Keywords: jasov

Gyulafirátót, avagy a rendi építészeti hagyományok átjárhatósága - Szakács, Béla Zsolt (Genius Loci. Laszlovszky 60, 2018)
(Gyulafirátót or the permeability of the monastic architectural traditions)
Keywords: gyulafirátót

A levéltárak titkos élete. A Csornai Premontrei Apátság levéltárainak évszázadai - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2018)
[The secret life of archives. Centuries of the archives of the Premonstratensian abbey of Csorna]
Keywords: csorna